A method for enhancing the interfacial bond strength of an optical fiber to a resin
Patent Information
- Application Number
- CN202611364132.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-23
AI Technical Summary
然而,单一纳米填料修饰方法虽然能够改善界面局部性能,但碳纳米管等纳米填料易团聚,难以均匀、稳定负载于光纤表面;单一金属有机框架材料虽然具有多孔结构和丰富功能位点,但其裂纹桥联和拔出耗能能力有限
本发明通过在光纤表面依次构筑硅烷偶联层和碳源/金属有机框架复合材料多尺度复合界面层,有效增加了光纤与树脂之间的实际接触面积和界面结合点密度。硅烷偶联剂与光纤表面形成稳定的Si-O-Si共价键,将化学惰性的光纤表面转化为富含活性官能团的反应性表面;MOF颗粒的多孔结构和粗糙形貌进一步增加了微观粗糙度和比表面积,为树脂固化过程中的分子链渗透和机械互锁提供了有利条件。实施例数据表明,经本发明改性后,界面剪切强度由单一硅烷改性时的5.56 MPa提升至12.99 MPa,提升率达133.6%。
Smart Images

Figure CN122958723A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite material interface modification technology, and in particular to a method for enhancing the interfacial bonding force between optical fiber and resin. Background Technology
[0002] With the development of aerospace, optical communication, smart structures, and structural health monitoring technologies, fiber optic sensors are widely used for strain, temperature, and damage monitoring in aerospace composite structures due to their advantages such as small size, light weight, resistance to electromagnetic interference, corrosion resistance, high sensitivity, and the ability to be embedded within composite materials. However, under actual service conditions, the interfacial properties between the optical fiber and the resin matrix directly determine the sensor's response accuracy and long-term service reliability.
[0003] Commonly used silica optical fibers are mainly composed of silica on their surface, which is relatively smooth and has limited chemically active sites. This results in weak interfacial bonding between the fiber and polymer matrices such as epoxy resin. Under conditions of composite material molding, cyclic loading, hot and humid environments, impact damage, or complex stress, interfacial debonding, slippage, and microcrack propagation can easily occur between the fiber and the resin. This reduces load transfer efficiency and affects the stability and reliability of embedded fiber optic sensing signals.
[0004] Existing technologies for improving the fiber / resin interface mainly include silane coupling agent treatment, acid-base etching, plasma treatment, polymer coating, and nanoparticle modification. Silane coupling agent treatment can form a certain molecular bridging effect between inorganic optical fibers and resins, but the resulting interface layer is usually thin and has a simple structural scale, offering limited improvement in interfacial mechanical interlocking and crack dissipation capabilities. While acid-base etching or high-energy plasma treatment can increase the surface roughness and active sites of the optical fiber, it may damage the surface of the silica optical fiber, introducing defects or microcracks, thereby reducing the fiber's mechanical strength and optical transmission stability.
[0005] Metal-organic frameworks (MOFs) possess high specific surface area, porous structures, and abundant functional sites. Among them, amino-functionalized titanium-based MOFs can form various interfacial interactions with optical fibers and epoxy resins through metal-oxygen cluster nodes and amino groups. Carbon nanotubes exhibit high strength, high modulus, and excellent crack bridging capabilities. However, while single nanofiller modification methods can improve local interfacial properties, nanofillers such as carbon nanotubes are prone to aggregation, making it difficult to uniformly and stably load them onto the optical fiber surface. Although single MOFs possess porous structures and abundant functional sites, their crack bridging and pull-out energy dissipation capabilities are limited.
[0006] Therefore, developing a fiber / resin interface enhancement method that does not damage the fiber's structure and sensing performance has significant practical application value for the development of aerospace, optical communication, smart structures, and structural health monitoring technologies. Summary of the Invention
[0007] The purpose of this invention is to provide a method for enhancing the interfacial bonding between optical fiber and resin. This method can construct a multi-scale composite interfacial layer, including silane coupling agent and carbon source / metal-organic framework, on the surface of the optical fiber without damaging the fiber's structure, thereby improving the interfacial bonding strength between the optical fiber and the resin matrix.
[0008] To achieve the above objectives, the present invention provides a method for enhancing the interfacial bonding force between optical fiber and resin, comprising the following steps: S1. Immerse the optical fiber in a silane coupling agent hydrolysate to silanize and modify it, thus obtaining a silanized optical fiber. S2. Mix the metal-organic framework precursor solution with the carbon source dispersion and perform a solvothermal reaction to obtain a carbon source / metal-organic framework composite material. S3. Add the carbon source / metal-organic framework composite material to a mixed solvent to obtain a carbon source / metal-organic framework composite dispersion, add silanized optical fiber, and heat treat to obtain a carbon source / metal-organic framework composite modified optical fiber. S4. Mix the carbon source / metal-organic framework composite modified optical fiber, resin, and curing agent, and cure to obtain the modified optical fiber / resin composite material.
[0009] In this invention, the optical fiber mentioned in S1 is a bare optical fiber after the external polymer coating layer has been removed. The type includes quartz optical fiber, with a core diameter of 9.3±0.4μm and a cladding diameter of 125±2μm, preferably HT-9 / 125. After obtaining the bare optical fiber, it is ultrasonically cleaned sequentially with acetone, ethanol, and deionized water. After cleaning, it is placed in an oven to dry for later use.
[0010] In this invention, the silane coupling agent hydrolysate in S1 is composed of a silane coupling agent and a hydrolysate, wherein the volume fraction of the silane coupling agent hydrolysate is 0.5% to 3% (based on the silane coupling agent), preferably 1%; the silane coupling agent includes one or more of aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, and methacryloyloxysilane coupling agents, preferably aminosilane coupling agents, and more preferably 3-aminopropyltriethoxysilane; the hydrolysate is an aqueous solution of an alcohol, wherein the volume ratio of alcohol to water is 7 to 19:1 to 3, preferably 9:1, and the alcohol is preferably ethanol.
[0011] In this invention, the preparation process of the silane coupling agent hydrolysate includes: mixing the silane coupling agent with the hydrolysate and stirring to obtain the silane coupling agent hydrolysate. The stirring temperature is 20~60℃, preferably 40℃, and the stirring time is 0.5~2h, preferably 1h.
[0012] In this invention, the silanization modification temperature in step S1 is 20~50℃, preferably 40℃, and the time is 0.5~3h, preferably 1h. After silanization modification, the system is dried in an oven to obtain the silanized optical fiber.
[0013] In this invention, the metal-organic framework precursor solution in S2 is composed of a metal-organic framework material and a mixed solvent; the metal-organic framework material has active groups and metal nodes capable of interacting with the surface of silanized optical fibers, the active groups including amino, carboxyl, or hydroxyl groups; the metal nodes include Ti, Zr, Zn, or Fe, preferably Ti; the mixed solvent is composed of N,N-dimethylformamide and methanol, the volume ratio of N,N-dimethylformamide to methanol being 3~9:1.
[0014] In this invention, the metal-organic framework material preferably includes the MIL series, UiO series, and ZIF series metal-organic framework materials, more preferably the MIL series, and even more preferably NH2-MIL-125.
[0015] In one embodiment of the present invention, the NH2-MIL-125 solution used is prepared experimentally. The preparation process includes: dissolving an organic ligand in a mixed solvent to obtain a ligand solution; adding a metal source to the ligand solution and stirring to obtain the NH2-MIL-125 solution. The organic ligand is 2-aminoterephthalic acid, the metal source is tetrabutyl titanate, and the molar ratio of the metal element in the metal source to the organic ligand is 1:1 to 4, preferably 1:2.
[0016] In this invention, the carbon source dispersion in S2 is composed of a carbon source and a dispersion. The carbon source includes one or more of hydroxylated carbon nanotubes, carboxylated carbon nanotubes, and aminated carbon nanotubes, preferably carboxylated carbon nanotubes, and more preferably carboxylated multi-walled carbon nanotubes. The dispersion includes N,N-dimethylformamide.
[0017] In this invention, the carbon source also includes at least one of graphene and carbon nanofibers.
[0018] In one embodiment of the present invention, the carbon source dispersion is prepared experimentally, and the process includes: placing the carbon source in the dispersion and stirring to obtain the carbon source dispersion.
[0019] In this invention, the temperature of the solvothermal reaction in S2 is 120~180℃, preferably 150℃, and the time is 12~36h, preferably 24h. After the solvothermal reaction is completed, the system is allowed to cool naturally to room temperature, and the product is washed and dried to obtain a carbon source / metal-organic framework composite material; the mass of the carbon source accounts for 0.1%~1% of the mass of the metal-organic framework precursor solution.
[0020] In this invention, the mixed solvent in S3 includes N,N-dimethylformamide and methanol, and the volume ratio of N,N-dimethylformamide to methanol is 3~9:1; the concentration of the carbon source / metal-organic framework composite dispersion is 0.1~10 mg / mL; the temperature of the heat treatment is 100~140℃, preferably 120℃, and the time is 8~24h, preferably 16h.
[0021] After the heat treatment was completed, the reaction system was naturally cooled to room temperature, and the heat-treated product was taken out and washed sequentially with N,N-dimethylformamide, methanol and deionized water to remove unbonded particles. Then the sample was placed in a vacuum oven and dried to obtain carbon source / metal-organic framework composite modified optical fiber.
[0022] In this invention, the resin in S4 includes epoxy resin, bismaleimide resin, phenolic resin, polyimide resin or vinyl ester resin, preferably epoxy resin; the mass ratio of the resin to the curing agent is 10:1 to 5, preferably 10:3.
[0023] This invention does not impose any special limitation on the type of curing agent; it can be selected according to the type of resin. Similarly, the curing method is not specifically limited; it can be selected accordingly based on the type of curing agent.
[0024] The present invention also provides a modified optical fiber / resin composite material prepared by the above method.
[0025] The present invention has the following beneficial effects: This invention effectively increases the actual contact area and interfacial bonding density between the optical fiber and the resin by sequentially constructing a silane coupling layer and a carbon source / metal-organic framework composite multi-scale composite interface layer on the optical fiber surface. The silane coupling agent forms stable Si-O-Si covalent bonds with the optical fiber surface, transforming the chemically inert fiber surface into a reactive surface rich in active functional groups. The porous structure and rough morphology of the MOF particles further increase the micro-roughness and specific surface area, providing favorable conditions for molecular chain penetration and mechanical interlocking during the resin curing process. Example data show that after modification according to this invention, the interfacial shear strength increases from 5.56 MPa with single silane modification to 12.99 MPa, an increase of 133.6%.
[0026] This invention further introduces a carbon source / metal-organic framework (MOF) composite interface layer on top of the silane coupling layer. The MOF particles form an uneven topological morphology on the optical fiber surface, with the carbon source intercalating between the MOF particles to form a one-dimensional bridging network. This transforms the optical fiber surface from a smooth plane to a multi-scale rough structure ranging from the molecular to the nano / micrometer scale, significantly enhancing the mechanical interlocking and bonding between the optical fiber and the resin, and improving the interface load transfer efficiency.
[0027] This invention introduces a carbon source / metal-organic framework (MOF) composite interfacial layer in the interface region, establishing multiple energy dissipation mechanisms: functionalized carbon nanotubes (hydroxylated, carboxylated, and aminated carbon nanotubes) act as crack bridging agents during interfacial crack propagation; CNTs spanning the crack plane consume a significant amount of fracture energy during pull-out or fracture; the CNT network promotes crack deflection, increasing the tortuosity of the crack propagation path; and MOF particles contribute additional energy dissipation through frictional sliding during interfacial debonding. Example data show that when the modified sample surface is covered with a large amount of resin residue and CNT-linked structures, the failure mode changes from simple interfacial debonding to a mixed failure mode, and the integral area of the load-displacement curve increases significantly.
[0028] This invention utilizes a silane coupling agent to form a self-assembled monolayer on the surface of an optical fiber, retaining outward-facing active sites. Next, functionalized carbon nanotubes are in-situ composited with a metal-organic framework (MOF). The spatial confinement effect of the MOF matrix is used to uniformly disperse the functionalized carbon nanotubes. Then, through electrostatic adsorption, hydrogen bonding, and coordination between the active sites and the active groups and metal nodes in the carbon source / metal-organic framework composite material, a chemically anchored stable loading of the composite reinforcement phase on the optical fiber surface is achieved, effectively avoiding the aggregation and shedding problems encountered during direct modification with the carbon source.
[0029] This invention employs a mild liquid-phase chemical treatment method throughout the process, with an operating temperature far below the softening point of the quartz optical fiber. It does not involve strong acid or alkali corrosion or high-energy particle bombardment. While effectively improving the interfacial bonding performance, it maintains the core structure and cladding integrity of the optical fiber, without introducing additional microcracks or stress concentration points, thus ensuring the tensile strength and optical transmission performance of the optical fiber.
[0030] The carbon source / metal-organic framework composite modified optical fiber prepared by this invention can be embedded in a resin substrate for interface enhancement and structural health monitoring of aerospace composite structures, smart composite structures and load-bearing components. Attached Figure Description
[0031] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0032] Figure 1 This is a flowchart illustrating the method for enhancing the interfacial bonding between optical fiber and resin provided in Example 1. Figure 2 SEM, EDS, and TEM images of the carbon source / metal-organic framework composite material prepared in Example 1; in, Figure 2 In the image, 'a' represents the SEM image at a scale of 1 μm. Figure 2 In the image, b represents the SEM image at a scale of 200 nm. Figure 2 In the diagram, c represents the EDS plot. Figure 2 In the image, d represents the TEM image at a scale of 500 nm. Figure 2 In this image, 'e' represents the TEM image at a scale of 100 nm. Figure 2 In the image, f represents the TEM image at a scale of 50 nm. Figure 2 In this image, g represents the TEM image at a scale of 20 nm. Figure 3 SEM images of the modified optical fiber / resin composite materials prepared in Example 1 and Comparative Example 1. in Figure 3 In the figure, 'a' is a SEM image of the modified optical fiber / resin composite material prepared in Comparative Example 1. Figure 3 In the image, b is the SEM image of the modified optical fiber / resin composite material prepared in Example 1; Figure 4 Comparison of AFM three-dimensional morphology and roughness of the modified optical fiber / resin composite material prepared in Example 1 and Comparative Example 1; in, Figure 4 In the figure, 'a' represents the AFM three-dimensional morphology and roughness diagram of the modified optical fiber / resin composite material prepared in Comparative Example 1. Figure 4 In the figure, b represents the AFM three-dimensional morphology and roughness diagram of the modified optical fiber / resin composite material prepared in Example 1. Figure 5 The graphs show the single-fiber pull-out test curves of the modified optical fiber / resin composite materials prepared in Example 1 and Comparative Example 1. Figure 6 The images show SEM images of the modified optical fiber / resin composite materials prepared in Example 1 and Comparative Example 1 after pull-out failure. in, Figure 6In the figure, 'a' represents the pull-out failure SEM image of the modified optical fiber / resin composite material prepared in Comparative Example 1 at a scale of 100 μm. Figure 6 In the figure, b is the pull-out failure SEM image of the modified optical fiber / resin composite material prepared in Comparative Example 1 at a scale of 50 μm. Figure 6 In the figure, c represents the pull-out failure SEM image of the modified optical fiber / resin composite material prepared in Example 1 at a scale of 100 μm. Figure 6 In the figure, d represents the pull-out failure SEM image of the modified optical fiber / resin composite material prepared in Example 1 at a scale of 50 μm. Detailed Implementation
[0033] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.
[0034] Example 1 This embodiment provides a method for enhancing the bonding force between optical fiber and resin interface, the process of which is as follows: S1. Select a quartz optical fiber with a cladding diameter of 125 μm (fiber model HT-9 / 125), remove the outer polymer coating layer to obtain the bare fiber; place the bare fiber in acetone, ethanol and deionized water for ultrasonic cleaning in sequence, each ultrasonic cleaning time is 10 min and the frequency is 68 kHz; after cleaning, place the fiber in an 80℃ oven to dry for 2 h, denoted as FO, for later use. Mix 1 mL of 3-aminopropyltriethoxysilane with 100 mL of hydrolysate (ethanol to water volume ratio of 9:1) and stir at 500 rpm for 1 h at 40 °C to obtain a 1% (v / v) silane coupling agent hydrolysate for later use. The optical fiber (FO) was immersed in a 1% (v / v) silane coupling agent hydrolysate and immersed at room temperature for 1 h for silanization modification. Then it was dried in an 80°C oven for 2 h to obtain silanized optical fiber, denoted as S@FO.
[0035] S2. Add 1.632 g of 2-aminoterephthalic acid to 30 mL of mixed solvent (N,N-dimethylformamide and methanol in a volume ratio of 7:1), and stir at 500 rpm for 20 min to dissolve it, obtaining a ligand solution; add 1.533 g of tetrabutyl titanate (the molar ratio of titanium to 2-aminoterephthalic acid in tetrabutyl titanate is 1:2), and continue stirring for 30 min to obtain a metal-organic framework precursor solution, denoted as NH2-MIL-125 solution, for later use; 30.9 mg of carboxylated multi-walled carbon nanotubes were added to 5 mL of N,N-dimethylformamide and dispersed by sonication at 68 kHz for 30 min to obtain a carbon source dispersion for later use. 30.9 g of metal-organic framework precursor solution and the carbon source dispersion prepared above were placed in a polytetrafluoroethylene-lined reactor and reacted solvothermically at 150 °C for 24 h. After the reaction was completed, the mixture was naturally cooled to room temperature. The product was washed and dried at 80 °C for 12 h to obtain a carbon source / metal-organic framework composite material.
[0036] S3. The carbon source / metal-organic framework composite material prepared above is added to a mixed solvent (N,N-dimethylformamide and methanol in a volume ratio of 7:1) and sonicated at 68 kHz for 20 min to obtain a carbon source / metal-organic framework composite dispersion. The silanized optical fiber prepared in S1 is tilted and fixed in a polytetrafluoroethylene-lined reactor, and the carbon source / metal-organic framework composite dispersion is added to completely immerse the silanized optical fiber. The reactor is sealed and heat-treated at 120 °C for 16 h. After the heat treatment, it is naturally cooled to room temperature. The heat-treated product is taken out and washed sequentially with N,N-dimethylformamide, methanol and deionized water to remove unbonded particles. The sample is then placed in a vacuum oven and dried at 70 °C for 2 h to obtain a carbon source / metal-organic framework composite modified optical fiber, denoted as CMS@FO.
[0037] S4. Epoxy resin (SWANCOR 2511-A) and curing agent (SWANCOR 2511-1BS) are mixed at a mass ratio of 10:3, and then vacuum degassed to obtain a resin mixture. The resin mixture is injected into a mold with dimensions of 1cm × 1cm × 2mm. The carbon source / metal-organic framework composite modified optical fiber is vertically embedded in the center of the mold, followed by staged curing to obtain the modified optical fiber / resin composite material, denoted as CMS@FO / EP. The staged curing process is as follows: pre-curing at 60℃ for 1 hour, followed by curing at 80℃ for 3 hours.
[0038] The flowchart of the method for enhancing the bonding force between optical fiber and resin interface provided in this embodiment is shown below. Figure 1 As shown.
[0039] Interface performance testing: Comparative Example 1 This comparative example provides a method for enhancing the interfacial bonding between optical fiber and resin, the process of which is as follows: S1. Select a quartz optical fiber with a cladding diameter of 125 μm (fiber model HT-9 / 125), remove the external polymer coating layer to obtain the bare fiber; place the bare fiber in acetone, ethanol and deionized water for ultrasonic cleaning in sequence, each ultrasonic cleaning for 10 min; after cleaning, place the fiber in an 80℃ oven to dry for 2 h, denoted as FO, for later use. 3-Aminopropyltriethoxysilane was mixed with hydrolysate (ethanol to water volume ratio of 9:1) and stirred at 40°C for 1 h to obtain a 1% (v / v) silane coupling agent hydrolysate for later use. The optical fiber (FO) was immersed in a 1% (v / v) silane coupling agent hydrolysate for 1 hour to perform silanization modification, and then dried in an 80°C oven for 2 hours to obtain silanized optical fiber, denoted as S@FO.
[0040] S2. Epoxy resin (SWANCOR 2511-A) and curing agent (SWANCOR 2511-1BS) are mixed at a mass ratio of 10:3, and then vacuum degassed to obtain a resin mixture. The resin mixture is injected into a mold with dimensions of 1cm × 1cm × 2mm, and the silanized optical fiber is vertically embedded in the center of the mold. Then, staged curing is performed to obtain a modified optical fiber / resin composite material, denoted as CMS@FO / EP. The staged curing process is as follows: pre-curing at 60℃ for 1 hour, followed by curing at 80℃ for 3 hours.
[0041] Characterization tests: A schematic diagram of the structure of the carbon source / metal-organic framework composite material (obtained in step S2) prepared in Example 1 of this invention is shown below. Figure 2 As shown. Figure 2 SEM, EDS mapping and TEM results show that MOF (metal-organic framework) was successfully loaded onto the surface of CNTs (carboxylated multi-walled carbon nanotubes). The C, N, O and Ti elements are uniformly distributed in the composite material, and a tight interfacial bond is formed between CNTs and MOF.
[0042] SEM images of the modified optical fiber / resin composite materials prepared in Example 1 and Comparative Example 1 of this invention are shown below. Figure 3 As shown. From Figure 3 It can be seen that CNTs@MOF (carbon source / metal-organic framework composite material) was effectively deposited on the substrate surface, and the modified surface changed from the original smooth surface to a rough structure with obvious particle accumulation.
[0043] The AFM three-dimensional morphology and roughness diagrams of the modified optical fiber / resin composite materials prepared in Example 1 and Comparative Example 1 of this invention are shown below. Figure 4 As shown. From Figure 4It can be seen that, compared with S@FO, CMS@FO has greater surface undulation and higher roughness, indicating that the composite modification layer was successfully constructed and significantly changed the surface micromorphology.
[0044] Performance testing: The interfacial shear strength of the modified optical fiber / resin composite materials prepared in Example 1 and Comparative Example 1 was evaluated using single-fiber pull-out tests. The results are shown in Table 1 and [Table data missing]. Figure 5 The interfacial shear strength is calculated using the following formula: ; Where Fmax is the maximum load during fiber pull-out, d is the fiber diameter, and le is the effective length of the fiber embedded in the resin matrix.
[0045] The pull-out failure morphology results for both are as follows: Figure 6 As shown.
[0046] Table 1. Results of interfacial shear strength test
[0047] From Table 1 and Figure 5 It can be seen that, compared with S@FO / EP, the CMS@FO / EP sample modified with carbon nanotube / metal-organic framework composite material exhibits a higher peak load and a larger load-displacement curve integral area, with an IFSS improvement rate of 133.6%, indicating that its interfacial load-bearing capacity and pull-out energy dissipation capacity have been improved.
[0048] Figure 6 The pull-out failure morphology results show that after the failure of the CMS@FO / EP sample, a lot of resin residue, interface layer residue and carbon nanotube entanglement structure can be observed on the surface of the optical fiber, indicating that its failure mode has changed from simple interface debonding to resin damage, interface layer damage and optical fiber / resin synergistic damage.
[0049] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for enhancing the interfacial bonding force between optical fiber and resin, characterized in that, Includes the following steps: S1. Immerse the optical fiber in a silane coupling agent hydrolysate to silanize and modify it, thus obtaining a silanized optical fiber. S2. Mix the metal-organic framework precursor solution with the carbon source dispersion and perform a solvothermal reaction to obtain a carbon source / metal-organic framework composite material. S3. Add the carbon source / metal-organic framework composite material to a mixed solvent to obtain a carbon source / metal-organic framework composite dispersion, add silanized optical fiber, and heat treat to obtain a carbon source / metal-organic framework composite modified optical fiber. S4. Mix the carbon source / metal-organic framework composite modified optical fiber, resin, and curing agent, and cure to obtain the modified optical fiber / resin composite material.
2. The method for enhancing the interfacial bonding between optical fiber and resin according to claim 1, characterized in that, The silane coupling agent hydrolysate described in S1 consists of a silane coupling agent and a hydrolysate, with the volume fraction of the silane coupling agent hydrolysate being 0.5% to 3%. The silane coupling agent includes one or more of aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, and methacryloxysilane coupling agents; The hydrolysate is an aqueous solution of alcohol, with a volume ratio of alcohol to water of 7~19:1~3.
3. The method for enhancing the interfacial bonding between optical fiber and resin according to claim 1, characterized in that, The silanization modification described in S1 is performed at a temperature of 20~50℃ for 0.5~3h.
4. The method for enhancing the interfacial bonding between optical fiber and resin according to claim 1, characterized in that, The metal-organic framework precursor solution described in S2 is composed of metal-organic framework materials and mixed solvents; The metal-organic framework material has active groups and metal nodes that can interact with the surface of silanized optical fibers. The active groups include amino, carboxyl, or hydroxyl groups; the metal nodes include Ti, Zr, Zn, or Fe. The mixed solvent is composed of N,N-dimethylformamide and methanol, wherein the volume ratio of N,N-dimethylformamide to methanol is 3 to 9:
1.
5. The method for enhancing the interfacial bonding force between optical fiber and resin according to claim 1, characterized in that, The carbon source dispersion described in S2 consists of a carbon source and a dispersion, wherein the carbon source includes one or more of hydroxylated carbon nanotubes, carboxylated carbon nanotubes, and aminated carbon nanotubes. The dispersion comprises N,N-dimethylformamide.
6. The method for enhancing the interfacial bonding force between optical fiber and resin according to claim 5, characterized in that, The carbon source also includes at least one of graphene and carbon nanofibers.
7. The method for enhancing the interfacial bonding force between optical fiber and resin according to claim 1, characterized in that, The solvothermal reaction described in S2 is carried out at a temperature of 120~180℃ for a time of 12~36h; The carbon source accounts for 0.1% to 1% of the mass of the metal-organic framework precursor solution.
8. The method for enhancing the interfacial bonding between optical fiber and resin according to claim 1, characterized in that, The mixed solvent in S3 includes N,N-dimethylformamide and methanol, wherein the volume ratio of N,N-dimethylformamide to methanol is 3~9:1; The concentration of the carbon source / metal-organic framework composite dispersion is 0.1~10 mg / mL; The heat treatment temperature is 100~140℃, and the time is 8~24h.
9. The method for enhancing the interfacial bonding force between optical fiber and resin according to claim 1, characterized in that, The resins mentioned in S4 include epoxy resins, bismaleimide resins, phenolic resins, polyimide resins, or vinyl ester resins; The mass ratio of the resin to the curing agent is 10:1~5.
10. A modified optical fiber / resin composite material prepared by the method according to claims 1 to 9.